Reactive Oxygen Species Activity and Antioxidant Properties of Fusarium Infected Bananas. Issue 4 (22nd February 2017) - Anthony, Kelvin Kiran; George, Dominic Soloman; Baldev Singh, Hasvinder Kaur; Fung, Shi Ming; Santhirasegaram, Vicknesha; Razali, Zuliana; Somasundram, Chandran
Abstract: Fusarium infection of bananas is a global problem that threatens the production of bananas. This study looks at the effects of the infection upon the reactive oxygen species (ROS) system, as well as the induced antioxidant properties in the roots, stems, leaves and fruits. Results show that there is a greater amount of damage in infected tissue samples as opposed to non‐infected. The damage was observed to be higher in the root samples. ROS assays were divided into two classes: ROS assays and ROS‐scavenging assays. Of the ROS assays, lipoxygenase was observed to be higher in the infected samples, while peroxidase (POD) and polyphenol oxidase (PPO) were significantly higher in infected stem, leaf and fruit samples. Among root samples, there was no significant difference in POD activity and PPO was lower in infected samples. Induction of ROS is important for the hypersensitive response (HR) to function properly. The ROS‐scavenging enzymes, namely ascorbate peroxidase, guaiacol peroxidase and superoxide dismutase, exhibited higher levels in the infected tissue. This is most likely to counter the build‐up of the ROS enzymes and to prevent further cell death. The increase in ROS‐scavenging assays also correlates with higher antioxidant properties as antioxidants play a critical role in regulating the HR free radicals.